2021
DOI: 10.3389/fpsyt.2021.778291
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Prenatal, Perinatal, and Family Factors for Anxiety Symptoms Among Preschool Children

Abstract: Anxiety is one of the most common psychological disorders among children. Few studies have investigated the prevalence and comprehensive factors for anxiety among preschool children in China. This study aimed to assess the prevalence of anxiety and explore influential factors at multiple levels including individual, prenatal and perinatal, and family factors, associated with anxiety symptoms among preschool children. The multisite cross-sectional study was conducted in Anhui Province and included 3,636 prescho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A multicenter study indicated that atopic dermatitis was observed most in the1-4 years’ groups ( 21 ). Previous studies indicated a strong association between allergic disease and lichen sclerosis ( 22 , 23 ). Considering allergic factors are risk factors of lichen sclerosis, allergic problems should receive more attention in preschool girls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A multicenter study indicated that atopic dermatitis was observed most in the1-4 years’ groups ( 21 ). Previous studies indicated a strong association between allergic disease and lichen sclerosis ( 22 , 23 ). Considering allergic factors are risk factors of lichen sclerosis, allergic problems should receive more attention in preschool girls.…”
Section: Discussionmentioning
confidence: 96%
“…A multicenter study indicated that atopic dermatitis was observed most Frontiers in Public Health 07 frontiersin.org in the1-4 years' groups (21). Previous studies indicated a strong association between allergic disease and lichen sclerosis (22,23).…”
Section: ) (C)mentioning
confidence: 99%
“…Globally, anxiety-related productivity losses are estimated at approximately $1 trillion per year [12]. Researchers suggest that preschool may be the optimal developmental window for anxiety prevention or early intervention [13,14].…”
Section: Introductionmentioning
confidence: 99%